2011
DOI: 10.1002/hyp.7807
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cross‐correlation patterns of European low, mean and high flows

Abstract: Low and high flows are associated with different hydrological processes. High flows correspond to the direct response of catchments to water input, whereas low flows occur in pronged dry periods and are governed by depleting storages. Therefore, the inter‐annual dynamics of high and low flows are often considered to be independent. To shed light on this assumption, we analysed a pan‐European dataset of 615 streamflow records, summarized as time series of annual streamflow percentiles (5th, 10th, …, 95th). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 185 publications
(199 reference statements)
0
41
0
1
Order By: Relevance
“…The fast reaction of runoff to precipitation corresponds to the findings of, for example, Haddeland et al (2011);Stahl et al (2012); Gudmundsson et al (2012). Based on their analysis of spatial cross-correlation patterns and runoff percentiles, Gudmundsson et al (2011Gudmundsson et al ( , 2012 conclude that discharge during dry conditions is largely influenced by terrestrial hydrological processes (catchment storage and release), in contrast to floods, which are mostly determined by forcing data. Stahl et al (2012) and Gudmundsson et al (2012) found that these terrestrial hydrological processes are poorly replicated in the simplified storage schemes of large-scale models.…”
Section: Storagementioning
confidence: 76%
“…The fast reaction of runoff to precipitation corresponds to the findings of, for example, Haddeland et al (2011);Stahl et al (2012); Gudmundsson et al (2012). Based on their analysis of spatial cross-correlation patterns and runoff percentiles, Gudmundsson et al (2011Gudmundsson et al ( , 2012 conclude that discharge during dry conditions is largely influenced by terrestrial hydrological processes (catchment storage and release), in contrast to floods, which are mostly determined by forcing data. Stahl et al (2012) and Gudmundsson et al (2012) found that these terrestrial hydrological processes are poorly replicated in the simplified storage schemes of large-scale models.…”
Section: Storagementioning
confidence: 76%
“…A good model performance with respect to interannual variability of all runoff percentiles (as reflected by relatively high R 2 ) is most likely related to the fact that the dynamics of annual runoff closely follow those of the atmospheric drivers. Shorthouse andArnell (1997, 1999), for example, have demonstrated the coupling between atmospheric oscillation indices and river flow in Europe, and recently Gudmundsson et al (2011b) showed that the dominant space-time patterns of European lowfrequency runoff variability (variability on time scales longer than 1 yr) were closely related to the corresponding patterns of precipitation and temperature. This dependence of runoff on atmospheric variability suggests that simulated runoff on interannual time scales may be more sensitive to the data product used to force the models than to the parameterization of terrestrial hydrological processes.…”
Section: Discussionmentioning
confidence: 98%
“…To provide insights into the entire flow range, two additional percentile series were introduced to characterize moderately low (Q 25 ) and high (Q 75 ) values. It can be argued that this set of five percentile series is sufficient to characterize the overall flow range, as previous results have demonstrated that the information gain by introducing additional percentile levels is limited for continental-scale analysis (Gudmundsson et al 2011a). This procedure resulted in a set of five time series of annual runoff percentiles for both observed and modeled runoff in each grid cell.…”
Section: Methodsmentioning
confidence: 98%
“…On these time scales runoff variability is known to have systematic continental scale space-time patterns (e.g. Lins, 1997;Gudmundsson et al, 2011) that are related to large-scale atmospheric drivers (e.g. Shorthouse and Arnell, 1997;Barlow et al, 2001;Tootle and Piechota, 2006).…”
Section: Introductionmentioning
confidence: 99%